Examining the effect of competitive intensity and organizational reserve on the relationship between innovation and company performance - Mohsen Rashidi; Mostafa Abdi; Maedeh Soumi (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The current changes in the fields of technology and issues formed at the level of society and companies have increased the importance of paying attention to the aspect of innovation in organizations. In this regard, the competitive situation of the market and the financial resources saved in the company can increase the conditions for improving the performance related to innovation. In other words, innovation is a primary factor in the organization's performance. This study aimed to investigate the effect of competition intensity and organizational reserve on the relationship between innovation and company performance.Methodology: The data required for this research was collected and analyzed using a questionnaire completed by 159 employees and company managers.Findings: The research results show a significant relationship between the intensity of competition and innovation. Also, the results indicate that organizational stock significantly affects innovation. Finally, the results of the third hypothesis of the research show that the intensity of competition and organizational reserve strengthen the relationship between innovation and performance.Originality/Value: Organizational reserve and intensity of competition are essential and influential factors in innovation, which improve the performance of the organization and its progress. Finally, increased innovation will help gain more profit and market share. Therefore, according to the research gap in the previous studies, the current research has investigated the effect of competition intensity and organizational reserve on the relationship between innovation and company performance.